Impact of Physical Activity on Psychological Distress: A Prospective Analysis of an Australian National Sample - del Pozo-Cruz, Jesus; del Pozo-Cruz, Borja; Perales, Francisco (My University, 2014)
Objectives. We analyzed the individual-level associations between participation in moderate to vigorous physical activity (MVPA) and psychological distress levels using a large, nationally representative, longitudinal sample and multivariable panel regression models. Methods. We used 3 waves of panel data from the Household, Income and Labour Dynamics in Australia Survey, consisting of 34 000 observations from 17 000 individuals and covering 2007, 2009, and 2011. We used fixed-effects panel regression models accounting for observable and unobservable confounders to examine the relationships between the weekly frequency of MVPA and summary measures of psychological distress based on the Kessler Psychological Distress Scale. Results. We found substantial and highly statistically significant associations between the frequency of MVPA and different indicators of psychological distress. Frequent participation in MVPA reduces psychological distress and decreases the likelihood of falling into a high-risk category. Conclusions. Our findings underscore the importance of placing physical activity at the core of health promotion initiatives aimed at preventing and remedying psychological discomfort.
American Journal of Public Health
Keywords: Health -- Physical activity; Health -- Mental; Health and wellbeing; Health; Physical activity; Mental; Health and wellbeing